Prevalence of obesity among women attending a Nigerian primary care clinic (2010)
The objective was to determine the prevalence of obesity and associated risk factors among women in a Nigerian Out-Patient clinic. A pre-tested structured questionnaire was administered on women at the General Outpatients’ Department (G. O. P.D) of the University College Hospital (U.C.H), Ibadan. The prevalence of obesity was 41.8%. Age was significantly associated with obesity, p=0.001. Majority of the obese participants (68.9%) in comparison to non-obese (46.4%) were traders, p=0.001. Many of the obese respondents were married (82.6%) in comparison to non-obese respondents who were widows (67.4%), p=0.001. Many of the obese respondents were multiparous (44.3%) having more than 4 children in comparison to the non-obese respondents with the highest proportion of women with no children (36.1%), p=0.001. Fewer of the obese women had no formal education (28.1%) and no primary education (26.4%), in comparison to the non-obese with 32.2% having secondary education and 27% having secondary education and 27% having post-secondary education, p=0.015. Majority of the obese women (62.3%) were pre-menopausal in comparison to the non-obese with 79.0% being pre-menopausal, p=0.001. Multivariate analysis done using logistic regression showed that risk factors for obesity included age group 50-59 years (odds Ratio 15.914, 95% CI=1.389-182.26, p=0.026), and being menopausal (Odds Ratio 1.452.95% CI=0.587-3.594, p=0.017). Having greater than five children was also found to be a risk factor for obesity (OR=3.321, 95%CI=1.236-8.921,p=0.017). The prevalence of obesity among Nigerian women remains high. There is a need to plan and implement measures for control.